HGG-61.Landscape of cancer predisposition in pediatric high-grade glioma. (3rd June 2022) - Blattner-Johnson, Mirjam; Sturm, Dominik; Sievers, Philipp; Jones, Barbara; Schramm, Kathrin; Balasubramanian, Gnana Prakash; Sill, Martin; Jäger, Natalie; van Tilburg, Cornelis M; Milde, Till; Pajtler, Kristian W; Dikow, Nicola; et al.
Abstract: Current estimates indicate that approximately 8–10% of cancer incidence in young patients can be attributed to constitutional alterations in genes linked to tumor initiation. The rarity and highly heterogeneous nature of high-grade glioma (HGG) in children and adolescents requires coordinated efforts to capture the diversity of subtypes in a normal-tumor matched sequencing cohort. Combining sequencing data of two registries based at the Hopp Children's Cancer Center (KiTZ) Heidelberg (INFORM and MNP2.0) allowed us to investigate the landscape of constitutional alterations across 350 children with high-grade gliomas. Both cohorts independently showed a surprisingly high proportion of patients (17%) with constitutional pathogenic alteration variants in cancer predisposition genes (n=40/233 and 23/128). Our results confirm a high frequency of alterations affecting genes of the DNA mismatch repair (MMR) pathway in 44% of IDH-mutant tumors (n=12/27). Additionally, we observed an almost exclusive correlation of MSH6 constitutional variation and somatic mutation in the IDH1 gene (n=7/8). A hypermutator phenotype defined by a tumor mutational burden >10 mutations/mb) was linked in 14/17 patients to a constitutional alteration in one of the following MMR genes: MLH1, MSH2, MSH6 or PMS2, with IDH-wildtype cases mostly classified as 'RTK1 subtype' by DNA methylation analysis. Constitutional alterations in TP53 were found in 5% of the total cohort. Furthermore, these tumors occurred exclusively in the group of H3-/IDH-wildtype glioblastoma (12%), and 8/18 tumors belong to the pedHGG_MYCN subgroup (conversely, this represents 40% of all 'MYCN subtype' patients, a highly significant enrichment over other subtypes (p<0.001). The overall high percentage of constitutional alterations in pediatric HGG warrants human genetics counselling for all affected patients and their families. Additionally, the strong correlation of MSH6 and IDH mutations as well as Li-Fraumeni-Syndrome and MYCN positive signature should be further explored as this might open the avenue for much needed new therapeutic approaches.